Varayti ng Wikang Sugbuanuong Binisaya sa Hilagang Cebu (Global Journal of Human-Social Science, 2018)
This study aims to describe the variety of the Sugbuanong Binisaya Language in Northern part pf Cebu particularly the morphological structures It specifically answers the following 1 words 2 meaning 3 types of morpheme 4 word forms 5 part of speech It anchored on the Sociolinguistic Theory and used qualitative method to analyze descriptively the data gathered Based on the data presented the variety of Sugbuanong Binisaya Language particularly the morphological structures describes the following most of the words are not the same spelling but some are the same the meaning of the words are the same there are two types of morpheme such as base morphemes and affixes word forms are simple words with affixes and compound words and part of speech such as nouns verbs adjective and adverbs The results of the study concluded that there are different varieties of Sugbuanong Binisaya Language in Northern part of Cebu in any situation That is why it recommends to further study about the phonology and syntax structures
Keywords: variety; wikang Sugbuanun’ Binisaya; morphological structures; words; meaning; types of morpheme; words forms and part of speech